Detection of microbial proliferation & assessment of antibacterial activity of spices collected from various locations of Dhaka city, Bangladesh (Stamford Journal of Microbiology, 2017)
The current study was aimed to detect the presence of contaminating microorganisms in some commonly available spices collected from different areas of Dhaka city, Bangladesh and also to assess their antibacterial activity. Out of eight samples under this study, total viable bacterial count (TVBC) was observed within the range of 106 to 107cfu/g. Among the specific bacterial isolates Staphylococcus spp., Pseudomonas spp. and Escherichia coli were found in almost all the samples within the margin of 102 to 106 cfu/g. Alarmingly Salmonella spp. and Vibrio spp. were presumptively identified in one and two samples respectively. Besides every sample showed the presence of fungus with load up to 103 cfu/g. Antibacterial activity of these samples was tested against seven laboratory isolates. Syzygium aromaticum showed highest activity against as many as five bacterial isolates while Cinnamomum verum was active against four isolates. On the other contrary, both Zingiber officinale and Laurus nobilis demonstrated their antibacterial activity only against Staphylococcus spp. and Klebsiella spp. respectively.Stamford Journal of Microbiology, Vol.7(1) 2017: 10-13